Maternal vaginal colonization and extended-spectrum beta-lactamase-producing bacteria in Vietnamese pregnant women - Viet, Nguyen Thanh; Van Du, Vu; Thuan, Nghiem Duc; Van Tong, Hoang; Toan, Nguyen Linh; Van Mao, Can; Van Tuan, Nguyen; Pallerla, Srinivas Reddy; Nurjadi, Dennis; Velavan, Thirumalaisamy P.; Son, Ho Anh (Antibiotics, 2021)
Extended-spectrum β-lactamase-producing Enterobacterales (ESBL-E) resistance to commonly prescribed drugs is increasing in Vietnam. During pregnancy, ESBL-E may predispose women to reproductive tract infections and increases the risk for neonatal morbidity. Vaginal colonization and infections by Escherichia coli and Klebsiella pneumoniae are seldom studied in Vietnam. In this study, we investigated ESBL-producing Enterobacterales in the birth canal of pregnant women. Between 2016 and 2020, vaginal swabs were collected from 3104 pregnant women (mean gestational age of 31 weeks) and inoculated onto MacConkey agar plates. Colonies were subjected to direct identification and antimicrobial susceptibility testing using the VITEK®-2 automated compact system and disk diffusion. ESBL production was determined phenotypically. E. coli, Klebsiella species were identified in 30% (918/3104) of the vaginal swabs, with E. coli being the most common (73%; 667/918). ESBL-production was detected in 47% (432/918) of Enterobacterales, with frequent multidrug-resistant phenotype. The overall prevalence of carbapenem resistance was low (8%). Over 20% of Klebsiella spp. were carbapenem-resistant. Pregnant women had a high prevalence of colonization and may transmit ESBL-E to neonates at birth, an important risk factor to be considered. The high rate of ESBL-producers and carbapenem resistance in Enterobacterales in Vietnam emphasizes the need for consequent surveillance and access to molecular typing.
Gesehen am 25.06.2021